Propiedades mecánicas, eléctricas y de durabilidad de concretos con agregados reciclados (2014)
The purpose of this master's degree in Civil Engineering, with emphasis on structures, was to evaluate the behavior of concrete with the replacement of coarse aggregate by aggregates of recycled concrete (ACR); this behavior was evaluated by evaluating some of the electrical, mechanical and durability properties of the mixtures made with this material. The ACR used in the different mixtures of the tests, was produced from the crushing of concrete specimens which had been tested in the laboratory of the Colombian School of Engineering. 8 different mixtures were evaluated with four different contents of recycled aggregates ( 0%, 25%, 50% and 100%) and two values ​​of water / cement ratio (0.5 and 0.6). Among the properties analyzed are the compressive strength, modulus of elasticity, resistivity, impedance, ultrasonic pulse velocity, chloride ion permeability, carbonation and sortividad.Los results of the tests clearly indicated that in the mixtures with higher percentage of recycled aggregate, the results of the modulus of elasticity and the resistance to compression are lower than for concrete with natural aggregate. The compressive strength of a concrete with 100% ACR has an estimated reduction of 20% to 25%, compared to a conventional concrete. At the same time, the electrical and durability properties measured by resistivity, impedance, yield and chloride ion permeability tests are affected by the increase in the percentage of recycled aggregate and the water / cement ratio.